Pengembangan E-modul Praktikum Fisika Virtual Materi Gerak Pada Kurikulum Merdeka - Purwanti, Popi; Fitrian, Andry; Andayanti, Westri; Ramadhani, Aulia Arba Chinta (UNIVERSITAS INDRAPRASTA PGRI, 2024)
In the learning process at our target school, practical activities are rarely conducted due to limited laboratory equipment and materials. One form of innovation in learning is the development of a virtual physics practicum e-module, particularly for motion material, as a guide for conducting practical activities. This research aims to (1) improve students' understanding of basic concepts of motion in physics using Crocodile Physics, (2) provide an interactive and engaging practicum experience using Crocodile Physics without being limited by the availability of physical equipment, (3) support the implementation of the Merdeka Curriculum by providing flexible and easily accessible learning resources, (4) encourage students' independent learning through modules that can be used independently or collaboratively in the classroom, and (5) attract students' scientific work skills to carry out practical activities accordingly. This research is a Research and Development (R&D) study with the ADDIE stages (Analysis, Design, Development, Implementation, Evaluation). Validation from each expert validator shows very good and good interpretation results. The response from students received an average of 85.60% with a very good interpretation. Significant improvement in students' scores in various aspects after using the e-module indicates that the e-module is effective in physics learning, especially in virtual practicum activities.